A carbonyl-rich covalent organic framework as a high-performance cathode material for aqueous rechargeable zinc-ion batteries. Issue 8 (8th February 2022) - Ma, Dingxuan; Zhao, Huimin; Cao, Fan; Zhao, Huihui; Li, Jixin; Wang, Lei; Liu, Kang
Abstract : A covalent organic framework (Tp-PTO-COF) with carbonyl active sites was proposed as a novel cathode material and successfully applied in aqueous rechargeable zinc-ion batteries (ZIBs). Abstract : Aqueous rechargeable zinc-ion batteries (ZIBs) provide high theoretical capacity, operational safety, low-cost and environmental friendliness for large-scale energy storage and wearable electronic devices, but their future development is plagued by low capacity and poor cycle life due to the lack of suitable cathode materials. In this work, a covalent organic framework (Tp-PTO-COF) with multiple carbonyl active sites is synthesized and successfully introduced in aqueous rechargeable ZIBs for the first time. Tp-PTO-COF delivers high specific capacities of 301.4 and 192.8 mA h g −1 at current densities of 0.2 and 5 A g −1, respectively, along with long-term durability and flat charge–discharge plateaus. The remarkable electrochemical performance is attributed to the abundance of nucleophilic carbonyl active sites, well defined porous structure and inherent chemical stability of Tp-PTO-COF. Moreover, the structural evolution and Zn 2+ ion intercalation mechanism are discussed and revealed by the experimental analysis and density functional theory calculations. These results highlight a new avenue to develop organic cathode materials for high performance and sustainable aqueous rechargeable ZIBs.